Palmier à huile : défis et questions à la recherche - Rival Alain (Oléagineux, Corps gras, Lipides, 2013)
Since several decades, the oil palm has been able to transform tropical landscapes and livelihoods. The oil palm is an outstanding oil crop producing very high oil yields and showing an amazing agronomic plasticity: these are valuable assets in a context of food safety and ecological intensification. The palm oil production now constitutes a global commodity chain which is at the focus point of North/South challenges such as certification, traceability or environmental and sanitary impacts. Palm oil is playing an increasing part in the production of edible oils; such an expansion must now comply with sustainability criteria backed by robust and shared scientific results. The sustainable development of oil palm cultivation thus generates many questions to research, not only in the traditional domains of plant science, but also in the fields of socio-economy and social and human sciences.